HUBUNGAN KEPATUHAN DAN DUKUNGAN KELUARGA DENGAN CLINICAL OUTCOME PASIEN TB - Mustaming Mustaming (Meditory : The Journal of Medical Laboratory, 2022)
Background: Tuberculosis is an infectious disease caused by mycobacterium tuberculosis. The low compliance of tuberculosis treatment caused resistance and affected clinical outcomes. Purpose: This study aimed to determine the relationship between medication compliance and family support with clinical outcomes in tuberculosis patients. Method: This analytical study used a cross-sectional design. The population was tuberculosis patients who used intensive phase of tuberculosis treatment at several primary health care. This study used a consecutive sampling technique. After we met the criteria and the patient signed informed consent, then microscopic smear and measurement of body weight were done to find clinical outcomes. After that, we gave a Medication Adherence Report Scale (MARS-5) questionnaire to measure medication compliance and a family support questionnaire to measure family support. The collected data were analyzed by fisher-test.Results: This study showed a relationship between medication compliance and clinical outcome with a p-value of 0.003 0.05. Respondents with high adherence had 16.625 times the possibility of achieving clinical outcomes compared to respondents who had low compliance. In addition, it was also found that there was a relationship between family support with clinical outcomes with a p-value of 0.006 0.05, and respondents with good family support had 11.333 times the possibility to achieve good clinical outcomes compared to respondents with sufficient family support. Conclusion: Hight medication compliance on treatment and good family support is essential in achieving good clinical outcomes at the end of the intensive phase.